2002
DOI: 10.2337/diacare.25.10.1691
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Insulin Monotherapy and Combination Therapy With Insulin and Metformin or Insulin and Troglitazone in Type 2 Diabetes

Abstract: OBJECTIVE—To evaluate the safety and efficacy of treatment with insulin alone, insulin plus metformin, or insulin plus troglitazone in individuals with type 2 diabetes. RESEARCH DESIGN AND METHODS—A total of 88 type 2 diabetic subjects using insulin monotherapy (baseline HbAlc 8.7%) were randomly assigned to insulin alone (n = 31), insulin plus metformin (n = 27), or insulin plus troglitazone (n = 30) for 4 months. The insulin dose was increased only in the insulin group. Metformin was titrated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
70
3
3

Year Published

2003
2003
2010
2010

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(84 citation statements)
references
References 49 publications
8
70
3
3
Order By: Relevance
“…However, metformin is known to positively affect other parameters which influence the development of cardiovascular disease, regardless of any effect on BP (30,31). Our results agree with the literature regarding the effect of metformin on BMI reduction (9,12,13), reduction of daily insulin dose (9,12,13), biguanide-related sideeffects (21,24), and reduction of WC, which is a cornerstone for the diagnosis of metabolic syndrome and may play the role of a co-variate when other parameters are analyzed (18,32).…”
Section: Other Parameterssupporting
confidence: 82%
See 3 more Smart Citations
“…However, metformin is known to positively affect other parameters which influence the development of cardiovascular disease, regardless of any effect on BP (30,31). Our results agree with the literature regarding the effect of metformin on BMI reduction (9,12,13), reduction of daily insulin dose (9,12,13), biguanide-related sideeffects (21,24), and reduction of WC, which is a cornerstone for the diagnosis of metabolic syndrome and may play the role of a co-variate when other parameters are analyzed (18,32).…”
Section: Other Parameterssupporting
confidence: 82%
“…The present study showed that the addition of metformin to a scheme of NPH insulin administered twice daily improved glycemic control of type 2 diabetic patients with the metabolic syndrome after 6 months, regardless of BMI reduction, as already shown in other studies (11,12). Although one study showed that metformin can lead to WC reduction (15), the improvement of A1C levels in our sample was independent of WC reduction, indicating that metformin improves sensitivity to the action of insulin by mechanisms already described, such as inhibition of hepatic gluconeogenesis (16).…”
Section: Glycemic Controlsupporting
confidence: 71%
See 2 more Smart Citations
“…However, as weight gain is an early event after initiation of insulin, the short-term effects of metformin on body weight may be relevant in the setting of concomitant insulin use. A number of these trials, listed in Table 2, 54-66 demonstrated significant reductions in body weight between patients receiving insulin and metformin compared with insulin and placebo 54,56,59,60,62 although other studies did not. 55,57,58,61,63,64 Two trials demonstrated Figure 1 Effects of randomized treatments on body weight in overweight patients in the UK Prospective Diabetes Study.…”
Section: Metformin and Weight A Golaymentioning
confidence: 99%